Retinoid X receptor-mediated neuroprotection via CYP19 upregulation and subsequent increases in estradiol synthesis. Issue 193 (October 2019) - Ishihara, Yasuhiro; Sakurai, Hikaru; Oguro, Ami; Tsuji, Mayumi; Vogel, Christoph F.A.; Yamazaki, Takeshi
Highlights: RXR stimulation in hippocampal slices. CYP19 upregulation by the promoter activation. Enhancement of estradiol synthesis. Neuroprotection mediated by attenuation of oxidative stress. Abstract: Increasing evidence has shown that one of the major neurosteroids, estradiol, has potent neuroprotective actions. We have reported that estradiol synthesis was enhanced when retinoic acid was added into rat hippocampal slice culture. In this study, we investigated the effects of a potent retinoid X receptor (RXR) agonist, bexarotene, on estrogen synthesis and neuroprotective action in hippocampal slices. Treatment with bexarotene increased estradiol levels as well as estrogen-synthesizing enzymes and CYP19 expression in hippocampal slice cultures. Bexarotene significantly suppressed neuronal cell death induced by oxygen-glucose deprivation (OGD)/reoxygenation. RXR agonists other than bexarotene, such as CD3254, also suppressed neuronal cell death accompanied by OGD/reoxygenation. The RXR antagonists HX531 and UVI3003 and the CYP19 inhibitor letrozole abolished the neuroprotection elicited by bexarotene, indicating that estradiol produced by RXR stimulation protects neurons from ischemic insult. The human brain-specific CYP19 promoter had 6 RXR half sites, and 2 of 6 half sites were responsible for CYP19 expression induced by bexarotene. Bexarotene increased the expression of catalase and glutathione peroxidase 1 and inhibited lipid peroxidation elicited by OGD/reoxygenation, suggesting that the antioxidative property of estrogen contributes to RXR-mediated neuroprotection. Bexarotene also suppressed neuronal injury induced by lipopolysaccharide in the hippocampal slices. Taken together, RXR stimulation can protect neurons via enhanced synthesis of estradiol with antioxidative mechanisms. The RXR-estrogen axis might be a novel mechanism-based strategy to prevent or ameliorate ischemic and/or inflammatory neuronal disorders.